AKAD MURABAHAH AND RAHN IN FINANCING PROGRAM OF PRODUCT GOLD MODEL LICENSE IN THE BANK SHARIA OF INDONESIA - Bulan Rohmadiyah; Lutvi Alamsyah (Institute of Research and Community Service, Institute of Pesantren Kiyai Haji Abdul Chalim, 2022)
Sell and buy gold in with cashless is product Installment Gold in PT. Bank Sharia of Indonesia, KCP Mojokerto. One of the most popular BSI products is the product BSI installment gold. Matter This is because the product is very profitable for people who want inv, vestment, gold ownership, and relatively stable gold prices. Because That researcher is interested in researching about Implementation contract Murabaha and Rahn installments of gold along with product suitability according to perspective DSN MUI No. 77/DSN-MUI/V/2010. The research type used is a field (field research) in PT Bank Sharia of Indonesia, KCP Mojokerto with a qualitative approach—the source of data in this study is from sources obtained through interviews and documents. From the r, results of these studies, it can be argued that the analysis results at PT Bank Sharia of Indonesia regarding the illegal buying and selling of gold cash are by the DSN-MUI Fatwa No.77/DSN-MUI/V/2010.